Evaluation of Learning in Primary Schools to Improve the Quality of Education - Nuansa Trimaya Fadhilla (PT Publikasiku Academic Solution, 2023)
The purpose of this study is to improve teacher professionalism and student achievement in elementary schools. This will also affect the educational institution. In general, evaluation is an effort made to determine the level of success and weakness of an educational process (with all components involved in it) in achieving the aspired educational goals. The purpose of education is to form human beings. Therefore, to find out whether the purpose of this education has been achieved or not, an evaluation is needed. Evaluation is useful to find out the quantity and quality of someone who needs to be evaluated. In addition, in the evaluation it is necessary to pay attention to several principles such as objectivity, continuity, and comprehensive or whole. This research method uses the library Researh method (literature study) with a qualitative approach. The results of this study show that the evaluation of learning outcomes in elementary schools covers three domains, namely the cognitive, affective and psychomotor domains.